Regional inequality and well-being of households in Kazakhstan: district- level analysis (Journal of Economic Research & Business Administration, 2024)
The importance of this study is that the first time in Kazakhstan the regional inequality is explained by the district level inequality by using household survey data, due to that regional inequality mainly studied by using only aggregate macroeconomic indicators before.  The main aim of this study using data from Kazakhstan Household Budget Surveys (KHBS) for the period from 2018-2021 to estimate decomposable measures of inequality on levels of regions and districts and identify which components (within or between regions inequality) are the main contributors to the income inequality.  To our knowledge there is a gap in literature in assessment of the effects of district level of inequality on well-being of households in Kazakhstan. The main significance of the paper is that   by applying Generalized Entropy indexes of inequality the study finds that rural inequality declines in that period. Which can be explained by distributional effects of Targeted Social Assistance policies. The methodology consists of the evaluation generalized entropy indexes on rural/urban, regions and districts level. Moreover, based on pooled OLS methodology for regressions analysis the main associates of well-being of households is estimated empirically. The results indicate that decomposition of inequality indicators illustrates that the portion of between groups inequality in total is greater for smaller areas such as districts (rayons) than for provinces (regions). The empirical model by application of annual Kazakhstan Household Budget surveys demonstrates that the effects of district inequality is significantly  and negatively affect to the  well-being of households, by taking into consideration  socio-demographic characteristics of households. Moreover, the location in more rich cities by macroeconomic indicators such as Almaty and Astana is negatively associates with well-being of households due to the district inequality. The main contribution of this work is that policymakers   have to pay more attention on district inequalities even in more prosperous regions in terms of macroeconomic indicators.Key words: district inequality, income distributions, decomposable inequality indexes, Kazakhstan, well-being of households.